Preparation, Pharmacokinetics, and Antitumor Potential of Miltefosine-Loaded Nanostructured Lipid Carriers [Retraction] - Yu G; Ali Z; Sajjad Khan A; Ullah K; Jamshaid H; Zeb A; Imran M; Sarwar S; Choi HG; Din F (International Journal of Nanomedicine, 2023)
Yu G, Ali Z, Sajjad Khan A, et al. Int J Nanomedicine. 2021;16:3255-3273. At the authors request, the Editor and Publisher of International Journal of Nanomedicine wish to retract the published article. Concerns were raised regarding the alleged duplication of images in Figures 9A, 9B and 9C with the same images from a previous article (ud Din et al, 2017 https://doi.org/10.1080/10717544.2016.1272651) by the same authors. Specifically,